2017
DOI: 10.33312/ijar.420
|View full text |Cite
|
Sign up to set email alerts
|

Family Ownership, Independent Oversight, and Financial Information Transparency: Evidence From Asia

Abstract: This study examines the association between family ownership and financial information transparency of large corporations in the Asian region and whether independent oversight (i.e., independent directors and external auditors) influences such relationship. The transparency of financial information is measured using earnings' opacity which includes three dimensions, i.e., profit aggressiveness, loss avoidance, and income smoothing. The findings show a positive association between family ownership and financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Using OLS estimation approach, it was found that managerial and institutional ownership had negative impact on tax avoidance strategies, but forgein ownership helped in promoting tax avoidance strategies. In case of Indonesia, Zulma (2016) estimated the link between management compensation and tax evasion by considering the effect of family ownership over 2011-2014 period. According to the findings, management compensation was negatively associated with tax avoidance but family ownership tended to reduce the negative relationship between tax avoidance and management compensation.…”
Section: Ownership Structure and Tax Avoidancementioning
confidence: 99%
“…Using OLS estimation approach, it was found that managerial and institutional ownership had negative impact on tax avoidance strategies, but forgein ownership helped in promoting tax avoidance strategies. In case of Indonesia, Zulma (2016) estimated the link between management compensation and tax evasion by considering the effect of family ownership over 2011-2014 period. According to the findings, management compensation was negatively associated with tax avoidance but family ownership tended to reduce the negative relationship between tax avoidance and management compensation.…”
Section: Ownership Structure and Tax Avoidancementioning
confidence: 99%
“…Asian Agri Group with defendant Suwir Laut in 2014 is a prime example of the most significant tax fraud case ever discovered in Indonesia (Pasliadja et al, 2014). This case has cost the government Rp2.6 trillion (Sitepu, 2017;Zulma, 2016). Another instance of tax evasion is the Bakrie Group mining firm (Sulistiyanti & Saputra, 2020;Zulma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This case has cost the government Rp2.6 trillion (Sitepu, 2017;Zulma, 2016). Another instance of tax evasion is the Bakrie Group mining firm (Sulistiyanti & Saputra, 2020;Zulma, 2016). This corporate group comprises PT Kaltim Prima Coal (KPC), PT Bumi Resources, and PT Arutmin Indonesia, which are implicated in IDR 2.1 trillion in tax evasion (Nurfaizah, 2016).…”
Section: Introductionmentioning
confidence: 99%